Neural EGFL like 1 as a potential pro-chondrogenic, anti-inflammatory dual-functional disease-modifying osteoarthritis drug. (January 2020) - Li, Chenshuang; Zheng, Zhong; Ha, Pin; Jiang, Wenlu; Berthiaume, Emily A.; Lee, Seungjun; Mills, Zane; Pan, Hsinchuan; Chen, Eric C.; Jiang, Jie; Culiat, Cymbeline T.; Zhang, Xinli; et al.
Abstract: Arthritis, an inflammatory condition that causes pain and cartilage destruction in joints, affects over 54.4 million people in the US alone. Here, for the first time, we demonstrated the emerging role of neural EGFL like 1 (NELL-1) in arthritis pathogenesis by showing that Nell-1 -haploinsufficient ( Nell-1 +/6R ) mice had accelerated and aggravated osteoarthritis (OA) progression with elevated inflammatory markers in both spontaneous primary OA and chemical-induced secondary OA models. In the chemical-induced OA model, intra-articular injection of interleukin (IL)1β induced more severe inflammation and cartilage degradation in the knee joints of Nell-1 +/6R mice than in wildtype animals. Mechanistically, in addition to its pro-chondrogenic potency, NELL-1 also effectively suppressed the expression of inflammatory cytokines and their downstream cartilage catabolic enzymes by upregulating runt-related transcription factor (RUNX)1 in mouse and human articular cartilage chondrocytes. Notably, NELL-1 significantly reduced IL1β-stimulated inflammation and damage to articular cartilage in vivo . In particular, NELL-1 administration markedly reduced the symptoms of antalgic gait observed in IL1β-challenged Nell-1 +/6R mice. Therefore, NELL-1 is a promising pro-chondrogenic, anti-inflammatory dual-functional disease-modifying osteoarthritis drug (DMOAD) candidate for preventing and suppressing arthritis-related cartilage damage.